2010
DOI: 10.1111/j.1574-6941.2010.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ammonia-oxidizing communities in barley-planted bulk soil and rhizosphere following nitrate and ammonium fertilizer amendment

Abstract: Oxidation of ammonia by nitrifying microorganisms is a major pathway that fertilizer nitrogen (N) may take upon application to agricultural soils, but the relative roles of bacterial (AOB) vs. archaeal (AOA) ammonia oxidizers are controversial. We explored the effects of various forms of mineral N fertilizer on the AOB and AOA community dynamics in two different soils planted with barley. Ammonia oxidizers were monitored via real-time PCR and terminal restriction fragment length polymorphism analysis of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 56 publications
5
40
2
Order By: Relevance
“…These indicate that the effects on soil ammonia-oxidizer communities in the subtropical plantation are stronger by deposited NH 4 þ À N than by deposited NO 3 À À N. First, it is because NH 4 þ -N fertilization directly increases soil NH 4 þ À N levels, and NH 4 þ /NH 3 serves as the direct substrate to ammonia monooxygense in NH 3 oxidation [50]. On the contrary, several studies documented that both NH 4 þ À N and NO 3 À À N fertilizations increased soil AOB abundances in the alpine meadow [35], and the farmlands [32]. These inconsistent results could be attributed to the differences of climatic regions (warm-wet vs. colddry), soil pH (acid vs. alkaline), and initial status of soil mineral N (e.g., [40].…”
Section: Effects Of N Addition On Ammonia-oxidizer Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These indicate that the effects on soil ammonia-oxidizer communities in the subtropical plantation are stronger by deposited NH 4 þ À N than by deposited NO 3 À À N. First, it is because NH 4 þ -N fertilization directly increases soil NH 4 þ À N levels, and NH 4 þ /NH 3 serves as the direct substrate to ammonia monooxygense in NH 3 oxidation [50]. On the contrary, several studies documented that both NH 4 þ À N and NO 3 À À N fertilizations increased soil AOB abundances in the alpine meadow [35], and the farmlands [32]. These inconsistent results could be attributed to the differences of climatic regions (warm-wet vs. colddry), soil pH (acid vs. alkaline), and initial status of soil mineral N (e.g., [40].…”
Section: Effects Of N Addition On Ammonia-oxidizer Communitiesmentioning
confidence: 99%
“…The effects of N additions on soil AOB abundance are controversial, including positive [30,34,35], negative [36], and neutral effects [27,28]. Moreover, few studies on the contrasting effects of soil NH 4 þ À N and NO 3 À À N enrichment on ammonia-oxidizer communities are available [37]. Few studies have investigated the relationships between ammonia-oxidizers and N 2 O emission in grassland [29,38] and agricultural soils [39].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the AOB abundance was more abundant in the N fertilization treatments than the control, AOA abundance decreased with increasing N fertilization rates. Glaser et al (2010) and Wu et al (2011) suggested that bacteria rather than archaea dominate ammonia oxidation in nearneutral or alkaline soils and in acidic soils, AOA play a more important role in ammonia oxidization (Zhang et al, 2012). From above literature reviews, it demonstrated that AOB and AOA may prefer to different ecological environments.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR (qPCR) targeting bacterial and archaeal amoA genes at selected time points of the incubation experiment was accomplished using an MX 3000 Real Time PCR system (Stratagene, La Jolla, CA). Amplification was carried out using the bacterial amoA primer set amoA1F/amoA2R and the archaeal amoA primer set Arch-amoAF/ Arch-amoAR (15). Standard curves for the archaeal and bacterial amoA genes were prepared by decimally diluting plasmids containing partial amoA amplicons to range from 10 9 to 100 copy numbers.…”
Section: Methodsmentioning
confidence: 99%